TINJAUAN PENGELOLAAN JARINGAN IRIGASI BENDUNG MENCONGAH KABUPATEN LOMBOK BARAT - ALFREDO VINCENSIUS DOWA BILLY; MUHAMAD YAMIN; AMINULLAH AMINULLAH (SOSIAL SAINS DAN TEKNOLOGI, 2021)
The  purpose  of  this  study  was  to  determine  the  water  balance,  and  water  supply  system  in  the  group  of  farmes  using  the  P3A  Mencongah  weir.  The  method  used  in  calculating  the  maximum  rainfall  is  the  Gumbel  method.  After  analyzing  the  availability  of  water  for  irrigation  on  the  Mencongah  Weir  irrigation  network  during  the  growing  season  it  is  fulfilled,  where  the  minimum  discharge  is  9,445  m3/sec,  while  the  water  demand  at  the  farmer  level  is  6.139  m3/sec.The  provision  of  water  at  the  farmer  level  during  the  growing  season  for  the  four  WUA  groups  (Water  User  Farmers  Assocoation)  at  Mencongah  Weir  continuously,  and  in  rotation